2004
DOI: 10.4049/jimmunol.173.9.5794
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Epigallocatechin-3-Gallate Mediates T Cellular NF-κB Inhibition and Exerts Neuroprotection in Autoimmune Encephalomyelitis

Abstract: Recent studies in multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE), point to the fact that even in the early phase of inflammation, neuronal pathology plays a pivotal role in the sustained disability of affected individuals. We show that the major green tea constituent, (−)-epigallocatechin-3-gallate (EGCG), dramatically suppresses EAE induced by proteolipid protein 139–151. EGCG reduced clinical severity when given at initiation or after the onset of EAE by both limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(209 citation statements)
references
References 35 publications
10
188
3
1
Order By: Relevance
“…Evidence for a pathogenic role of ROS in MS pathology has led to the employment of several antioxidant strategies in an effort to ameliorate EAE (293,300,301). With the acceptance of the possibility that active oxidative stress contributes to the disease process, there is increasing focus on developing therapies directed at upregulating antioxidant enzyme systems (302,303) or production of endogenous antioxidants (304).…”
Section: Role Of Oxidative Stress In Msmentioning
confidence: 99%
“…Evidence for a pathogenic role of ROS in MS pathology has led to the employment of several antioxidant strategies in an effort to ameliorate EAE (293,300,301). With the acceptance of the possibility that active oxidative stress contributes to the disease process, there is increasing focus on developing therapies directed at upregulating antioxidant enzyme systems (302,303) or production of endogenous antioxidants (304).…”
Section: Role Of Oxidative Stress In Msmentioning
confidence: 99%
“…In support of this, recent animal studies have shown that green tea intake helps to prevent age-related cognitive deficits (Table 2), particularly after long-term administration of green tea (approximately 6 months), which was shown to positively influence memory and learning in both normally aged and senescence-accelerated animals (96,146,160) . Tea flavonoids have been reported to be potent Fe chelators, radical scavenging agents and to have antiinflammatory activities (161)(162)(163)(164)(165)(166) . In addition to these effects, recent studies have also indicated that they are capable of modulating signal transduction pathways and of regulating gene expression, and that these effects may also contribute to the neuroprotective effects of these compounds (29,167) .…”
Section: Green Teamentioning
confidence: 99%
“…Neuroprotection as a Therapeutic Target for MS. Neural damage in MS could be directly due to inflammation (43) or result from loss of trophic support normally provided to axons by myelin or glia. Consequently, neuroprotection is considered a novel target for MS, and different drugs and molecules, including statins, green tea epigallocatechin-3-gallate, and erythropoietin (44)(45)(46), have been indicated as effective in experimental models of the disease. Here, we indicate that chronic administration of selective acetylcholinesterase inhibitors that are approved for AD treatment, at a dosage effective in increasing acetylcholine release in the hippocampus and cortex of aged rats (21), restores ChaT activity and performance in the water maze test in EAE rats.…”
Section: Cns Inflammation and The Cholinergic System Of The Basal Formentioning
confidence: 99%